Intervention Fidelity Within Trials of Infant Feeding Behavioral Interventions to Prevent Childhood Obesity: A Systematic Review. Issue 1 (9th May 2018) - Toomey, Elaine; Matvienko-Sikar, Karen; Heary, Caroline; Delaney, Lisa; Queally, Michelle; Hayes, Catherine B; Kearney, Patricia M; Byrne, Molly; ,
Abstract : Strategies to enhance and assess fidelity within trials of infant feeding interventions have been used/reported to a moderate extent, suggesting that previous findings of inconsistent effectiveness of such interventions may not fully reflect the intended interventions. Abstract: Background: Intervention fidelity refers to whether an intervention has been implemented as intended. Trials of infant feeding behavioral interventions to prevent childhood obesity show inconsistent evidence of effectiveness. However, intervention fidelity has not been previously explored within these trials, limiting interpretation of findings. Purpose: To review the use and/or reporting of strategies to enhance and assess intervention fidelity within trials of infant feeding interventions to prevent childhood obesity, and their association with study quality, effectiveness, and publication year. Methods: Seven electronic databases were searched, with articles screened for inclusion by two reviewers. The National Institutes of Health Behaviour Change Consortium fidelity checklist was used to assess use and/or reporting of fidelity strategies across five domains (design, provider training, delivery, receipt, and enactment). Results: Ten trials (16 papers) were identified. Average use/reporting of fidelity strategies was moderate (54%), ranging from 28.9% to 76.7%. Levels of use/reporting ranged from 15.9% in the domain of provider training to 95% for enactment. No association was found between these levels and study quality, effectiveness, or publication year. Conclusions: The moderate use/reporting of fidelity strategies within trials of infant feeding interventions suggests that previous findings of inconsistent effectiveness may not fully reflect the intended interventions. The review highlights key considerations for improving future research, both in the area of behavioral infant feeding and wider behavior change literature. This includes improving reporting across all fidelity domains and ensuring an enhanced focus on provider training and control group content to optimize the translation of research into practice. PROSPERO Registration number: CRD42016033492.